Loss of epidermal Langerhans cells in psoriasiform lesions of de novo induced or worsened pre‐existing psoriasis following uses of immune checkpoint inhibitors. Issue 9 (12th May 2022) - Kase, Misaki; Fujita, Yasuyuki; Ota, Asako; Shimizu, Satoko; Itoi‐Ochi, Saori; Sano, Shigetoshi
Abstract: Immune checkpoint inhibitors (ICI), including monoclonal antibodies to programmed death 1, programmed death ligand 1, and cytotoxic T lymphocyte‐associated antigen 4, have provided great therapeutic benefits for cancer patients at advanced stages. However, the introduction of ICI frequently results in the development of immune‐related adverse events (irAE) through activation of autoreactive T cells. Here, we present three cases of cancer patients with cutaneous irAE, including development of de novo psoriasis and exacerbation of pre‐existing psoriasis. Interestingly, these patients shared an altered histological feature characterized by loss of epidermal CD1a + cells, namely Langerhans cells (LC), in the psoriasiform lesions in contrast to "conventional psoriasis" exhibiting unchanged or activated LC. A possible underlying mechanism was that ICI‐mediated hyperactivation of effector T cells contributed to aggravation or establishment of psoriasis phenotype, which might be associated with direct cytotoxicity or expulsion of LC from the epidermis.